Prevalence and Prognostic Significance of Fragmented QRS Complex in Middle-Aged Subjects With and Without Clinical or Electrocardiographic Evidence of Cardiac Disease - Terho, Henri K.; Tikkanen, Jani T.; Junttila, Juhani M.; Anttonen, Olli; Kenttä, Tuomas V.; Aro, Aapo L.; Kerola, Tuomas; Rissanen, Harri A.; Reunanen, Antti; Huikuri, Heikki V. (The American journal of cardiology, 2014)
We wanted to evaluate the prevalence and prognostic value of the fragmented QRS (fQRS) complex, defined as changes in QRS morphology with various RSR′-patterns in 12-lead electrocardiogram (ECG) in a middle-aged general population. We evaluated the 12-lead ECGs of 10,904 Finnish middle-aged subjects (52% men, mean age 44 ± 8.5 years) with (n = 2,543) and without (n = 8,361) an evidence of cardiac disease drawn from general population and followed them for 30 ± 11 years. Fragmentation of the QRS complex was defined as various RSR′-patterns in at least 2 consecutive leads within the same territory (inferior II, III, aVF; lateral I, aVL, V4 to V6; anterior V1 to V3). Primary end points were death from any cause, cardiac, and arrhythmic deaths. In the total population, fQRS was present in 19.7% (n = 2,147) of subjects, including 15.7% (n = 1714) in inferior leads, 0.8% (n = 84) in lateral leads, and 2.9% (n = 314) in anterior leads. Fragmentation was not associated with increased mortality in subjects without a known cardiac disease. However, fQRS observed in lateral leads in subjects with an evidence of cardiac disease was associated with an increased risk of all-cause (p = 0.001), cardiac (p = 0.001), and arrhythmic (p = 0.004) mortalities. In conclusion, fQRS reflecting minor intraventricular conduction defect is a common finding, especially in the inferior leads, but it is not a sign of increased risk of mortality in subjects without a known cardiac disease. Lateral fQRS, which is less commonly observed in the ECG, is associated with a worse outcome in patients with a known cardiac disease.